Interpersonal Communication of Caregivers in Increasing the Independent Activities of Daily Life of the Elderly in Nursing Homes - Yuningsih, Aneng; Suprapti, Betty; Somana, Aan (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: The older a person gets, the more their physical abilities will decrease, thus causing dependency in carrying out Activity Daily Living (ADL). Elderly people who live in nursing homes will be assisted by caregivers, therefore the use of appropriate communication is very necessary. Objective: This study aims to determine the role of caregivers' interpersonal communication in increasing the ADL independence of elderly people in nursing homes. Method: This research used a qualitative method with 2 caregivers and 2 elderly informants selected based on purposive techniques. Data collection techniques were carried out using observation, in-depth interviews, and document studies as well as descriptive data analysis techniques using percentages. Result: Based on the research results and discussion, it can be concluded in this research as follows: (1). Overall, the role of caregivers interpersonal communication in increasing the ADL independence of the elderly is concluded to be quite good. (2). The language used by caregivers is very appropriate in communicating with the elderly. (3). Non-verbal communication carried out by caregivers in interacting with the elderly is by using movements, gestures, facial expressions, symbols and varied voice intonations. (4). The message conveyed in the caregiver's interpersonal communication with the elderly is more about the concept of learning and motivating the elderly to more quickly understand what the caregiver means. Conclusion: There is a need for training in interpersonal communication techniques specifically for the elderly for nursing home caregivers or other parties who may interact intensively with the elderly.